Projeto APAE: Um passeio de inclusão para Jaguarão- RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Accessibility is a right of all people, and the tourism sector needs to invest in projects that enable the participation of all. Thus, this project aims to organize an accessible script for the students of Early Childhood Education of APAE de Jaguarão-RS. The methodology used to develop this project was, as far as the approach, a qualitative research; of an applied nature; objectives was descriptive; and the procedures were bibliographic, field research and case study. We analyzed some tourist points of the city of Jaguarão-RS, to verify the accessibility infrastructure. Also, in order to reach the needs of the target public identified as a group of 2nd and 3rd year students of APAE Jaguarão-RS, the following subjects were also studied: accessibility, tourist routes and routes, accessible tourism, history of Jaguarão-RS and destinations with accessible tourism. Thus, after considering the needs of participants and the sights of the city, an accessible road map for APAE students was drawn up.
Keywords: Acessibilidade; Roteiro; Turismo; Associação de Pais e Amigos dos Excepcionais (Jaguarão, RS); Accessibility; Route; Tourism; Association of Parents and Friends of the Exceptional (Jaguarão, RS); CNPQ::CIENCIAS SOCIAIS APLICADAS